(untitled) (Research, Society and Development, 2022)
This study was conducted to examine the problems of the Foundation’s dispute in connection with the amendment to the articles of association that use the same name, as well as to examine the legal protections for the Foundation’s organs with legal standing. The research method employed was normative legal. The goal of this method is to evaluate the benefits of legislation for legal subjects, rights and obligations, legal events, legal relations, and legal objects. The data was collected in the form of literary data by collecting primary legal materials such as laws and court decisions, as well as secondary legal materials such as books, journals, and documents. The qualitative data analysis technique was used to provide an assessment of the implementation of Law Number 28 of 2004 concerning Amendments to Law Number 16 of 2001 concerning Foundations in terms of the legal protection of Foundation organs. According to the study’s findings, changes to the articles of association made by a foundation organ with legal standing will provide legal protection and certainty. A notary who makes a deed of amendment to the articles of association of the foundation inaccurately results in the deed being canceled.